Mechanics of masonry in compression : results from a homogenisation approach - Zucchini, Alberto (2007)
Despite considerable experimental and analytical research in the past, modern regulations still adopt very conservative simplified formulas for the compressive strength of masonry. The present paper contributes to the understanding of masonry under compression, using a novel non-linear homogenisation tool that includes the possibility of tensile and compressive progressive damage, both in the unit and mortar. The simplified homogenised model uses an iterative procedure and a few ingenious micro-deformation mechanisms, being able to accurately reproduce complex simulations carried out with non-linear continuum finite element analysis, at a marginal cost of CPU time and with no convergence difficulties. In addition, the comparison of the model with experimental results available in the literature indicates that an estimation of the compressive strength of masonry better than the one provided by the codes is possible, using the mechanical and geometrical properties of the masonry components.